Factors influencing evidence based librarianship (EBL) practices among Malaysian academic librarians / Ida Nadia Mohamad Bahtiar - Mohamad Bahtiar, Ida Nadia (2020)
Evidence based librarianship (EBL) supports librarians in problem solving and decision making process. This concept provides additional value to a library in numerous aspects of librarianship activities and services. EBL supports librarians in applying evidence approach in their daily practices since the concept is moderately flexible and applicable in many areas of the library. The purpose of this study is to examine the factors that may influence the adoption of Evidence based librarianship (EBL) by librarians in Malaysia’s Public Higher Learning Institutions. The present study adopts quantitative approach and employs survey as the research instrument. The target population was among libraries from Malaysian public universities and 234 questionnaire forms were distributed to 234 out of the total population of 624 librarians. This study involves main research variables such as: Organizational factor, Research utilization factor, Diffusion of innovation factor, Job design factor and adoption of EBL. The findings of the study shows that librarians indicate positive signs to the sources and the use of evidence in the libraries. They employ evidence in their day to day practice, however, the adoption of EBL in Malaysia was at an average level. The moderate level of evidence act ivities in library indicates the consequences of EBL in enhancing the efficiency of operation and services of Malaysian Public Higher Learning Institutions libraries. In term of the relationship study, the results demonstrate a positive and significant relations to the four factors in which the variables are directly related to the adoption of EBL. Overall, it shows that librarians are lacking in assessing the EBL skills to fulfil users’ needs and demands. By attending suitable EBL training, it will enable to further develop competency, increasing capabilities and creativities to utilize new and innovative ideas. The existing resources in the library can be used to enhance librarians’ productivity and effectively supporting their daily tasks. The outcome of the study contributes to the EBL practice specifically in Malaysian Public Higher Learning Institutions libraries. It can be used as guidance to individuals who have interest in evidence practices and for those seeking knowledge on EBL in the Malaysian context. Previous study found that EBL is able to support effective decision making and contributes to the reduction of risks.